THE INFLUENCE OF PROFITABILITY, CAPITAL STRUCTURE, INVESTMENT DECISION, AND FIRM SIZE ON FIRM VALUE (A Study in the Pharmaceutical Sector Listed on the Indonesian Stock Exchange) - Chairil Akhyar; Hepi Boang Manalu; Husaini; Wardhiah (PT. Radja Intercontinental Publishing, 2023)
This study examines the influence of profitability, capital structure, investment decisions, and firm size on firm value in pharmaceutical sub-sector companies on the Indonesia Stock Exchange. This study uses secondary data from the financial statements of each pharmaceutical sub-sector company. The sample in this study consists of 9 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during 2018-2021. The data analysis method used is a multiple linear regression test with the help of Eviews 12. The results partially show that return on assets, return on equity, and capital structure has a positive and significant effect on firm value. Meanwhile, investment decisions and firm size partially do not significantly affect firm value in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period.